P082 A cell-centred meta-analysis reveals baseline predictors of anti-TNFα non-response in biopsy and blood of IBD patients. (16th January 2018) - Gaujoux, R; Starosvetsky, E; Maimon, N; Vallania, F; Bar-Yoseph, H; Pressman, S; Weisshof, R; Goren, I; Waterman, M; Yanai, H; Dotan, I; Sabo, E; et al.
Abstract: Background: Although anti-TNFα therapies represent a major breakthrough in inflammatory bowel diseases (IBD) therapy, their cost-benefit ratio is hampered by an overall 30% non-response rate, adverse side effects and high costs. Thus, finding predictive biomarkers of non-response prior to commencing anti-TNFα therapy is of high-value. Methods: We analysed publicly available whole-genome expression profiles of colon biopsies obtained from multiple cohorts of IBD patients using a combined computational deconvolution – meta-analysis paradigm which allows to estimate immune cell contribution to the measured expression and capture differential regulatory programs otherwise masked due to variation in cellular composition. Insights from this in-silico approach were experimentally validated in biopsies and blood samples of three independent test cohorts. Results: We found the proportion of plasma cells as a robust pretreatment biomarker of non-response to therapy, which we validated in two independent cohorts of immunostained colon biopsies, where a plasma cellular score from inflamed biopsies was predictive of non-response with an Area Under the Curve (AUC) of 87.5%. Meta-analysis of the cell proportion-adjusted gene expression data suggested that an increase in inflammatory macrophages in anti-TNFα non-responding individuals is associated with the upregulation of the TREM1 and CCR2-CCL7 axes. Blood gene expression analysis of an independent cohort, identified TREM1 downregulation in non-responders at baseline, which was predictive of response with an AUC of 94%. Conclusions: Our study proposes two clinically feasible assays, one in biopsy and one in blood, for predicting non-response to anti-TNFα therapy prior to initiation of treatment. Moreover, it suggests that mechanism-driven novel drugs for non-responders should be developed.